Composition of Aiginates from Brown Seaweeds, Sargassum and Padina spp. - Omar, Siraj; Ahmad, Norasmah; Ahmad, Fashihuddin (1988)
The percentage yield of alginate in brown seaweeds, Sargassum and Padina spp., from Sabah, and the intrinsic viscosities of these alginates were determined. Young and mature Sargassum, respectively, gave 35% and 32%, while Pad ina only yielded 18.5% of alginate. The intrinsic viscosities [TIl, obtained were 412 mL/g and 312 mL/g foralginates from mature SargassumandPadina, respectively. It was found that these intrinsic viscosities depend on the source and species of seaweeds. Treating the alginate sample with bleaching agent such as NaOC1 yielded samples with [TIl =210 mL/g. However, a higher intrinsic viscosity, [TIl = 650 mL/g, was obtained from Sargassum samples which were pre-treated in dilute formaldehyde solution. Results from intrinsic viscosity determination were used to estimate the viscosity average molecular weight, Mv' of the phycocolloid using the Mark-Houwink equation. Block compositions of alginates were determined using the technique ofpartial heterogenous hydrolysis. Results showed that young Sargassum was richer in the poly (I3-D-mannuronate) block, while matured Sargassllm 1.27, 0.64 and 0.85 for alginates from young Sargassum, mature Sargassum and Padina, respectively. This shows that mature Sargassum yields alginates with the lowest MIG ratio. was richer in the poly (a-L-guluronate) block. From these compositions, M/G ratios were estimated as 1.27, 0.64 and 0.85 for alginates from young Sargassum, mature Sargassum and Padina, respectively. This shows that mature Sargassum yields alginates with the lowest MIG ratio.